2003
DOI: 10.1093/ageing/afg101
|View full text |Cite
|
Sign up to set email alerts
|

Onset of mobility disability among community-dwelling old men and women. The role of tiredness in daily activities

Abstract: older people who complain about tiredness are at higher risk of becoming disabled than others. This highlights the need for alertness and management of this early sign of functional decline in a preventive perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 30 publications
1
79
2
2
Order By: Relevance
“…These findings are consistent with those of Dzurec (147), who reported that interpersonal relationships play a vital role in women's experience of fatigue and may in fact ex- Fatigue may also be seen as a kind of chronic reaction to the accumulated chronic strain of dealing with the effects of cumulated social stress throughout life, in addition to the physiological and biological decline which characterizes aging. However, it does not attenuate the associations between fatigue and functional decline to adjust by socio-economic factors (33,34,58,59) and social relations (33,58,59).…”
Section: Importance Of Life-course Factorsmentioning
confidence: 96%
“…These findings are consistent with those of Dzurec (147), who reported that interpersonal relationships play a vital role in women's experience of fatigue and may in fact ex- Fatigue may also be seen as a kind of chronic reaction to the accumulated chronic strain of dealing with the effects of cumulated social stress throughout life, in addition to the physiological and biological decline which characterizes aging. However, it does not attenuate the associations between fatigue and functional decline to adjust by socio-economic factors (33,34,58,59) and social relations (33,58,59).…”
Section: Importance Of Life-course Factorsmentioning
confidence: 96%
“…Increasing age is associated with a risk of ADL problems (e.g., Allen et al 2001;Covinsky et al 2003;Fauth et al 2008;Hellström and Hallberg 2001;Iwarsson 2005). Gender has also been demonstrated to affect self-reported functional ability (e.g., Ahacic et al 2003;Hellström and Hallberg 2001;Reynolds and Silverstein 2003;Romören and Blekeseaune 2003), with most studies showing greater self-reported ADL problems among women than men (e.g., Avlund et al 2003;Puts et al 2005;von Strauss et al 2003). Married individuals are also less likely to report ADL problems (e.g., Avlund et al 2002;Hallberg and Lagergren 2009), perhaps because they receive occasional assistance from a spouse which supports continued independence.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature confirms that limitations in mobility may lead to restricted social participation. [28,57,58] As a result, professional caregivers should be aware that mobility-disabled residents are likely to need elaborate help with their social participation. Also, the nursing home residents should be educated about this association to be prepared for a possible connection between their mobility disability and their need for support in their social participation.…”
Section: Hypothesismentioning
confidence: 99%